Small and Medium Enterprises’ Risk Modeling - Sorooshian, Shahryar; Ahmad Suffian, Nursofea Iman (IRMM, 2017)
Small and medium enterprises (SMEs) in Malaysia keep failing year to year due to economic fluctuation and challenges. This affects the industry and economy growth of Malaysia. This research was conducted to identify criteria of performance prediction model that can predict success or failure risk of SMEs and to develop the predictive model, based on logit regression method, for SMEs of Malaysia. Developing a model of logit regression is by using the four perspectives of the balanced scorecard approach. The four perspectives are independent variables, including the success and failure of SMEs as the dependent variable. The variables would help in developing the model through Statistical Package for the Social Science. data software to gain the binomial regression results. The modeled result is based on the probability of the SME success and bankruptcy risk, useful for policy makers.